Gamification integration module (smart receipt mobile application) - Teo, Jia Hao (2018)
With the ongoing increase of technological improvement and reliance on mobile phones in the world, mobile applications are developed every day to meet certain needs. However, not every application has a long lifespan and tend to drop off in the short run due to various reasons.